1999
DOI: 10.2170/jjphysiol.49.159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C and E in Modulating Peripheral Vascular Response to Local Cold Stimulus in Man at High Altitude.

Abstract: At high altitude (HA), cold stress is aggravated by hypoxia, perhaps due to the increased formation of free radicals which trigger oxidative stress. This may be one of the contributing factors for adverse effects including disturbances in microcirculation and capillary permeability resulting in decreased peripheral blood flow. This leads to altered cold-induced-vasodilatation (CIVD) response on exposure to HA. The present study was conducted on 40 male volunteers (4 groups of 10 each) to evaluate the utility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 0 publications
1
23
1
Order By: Relevance
“…It may appear that current results are in conflict with previous studies that have shown an enhanced cold-induced vasoconstriction during CWI of a hand at high-altitude (Daanen and van Ruiten, 2000;Mathew et al, 1977;1979;Purkayastha et al, 1999;Takeoka et al, 1993). However, in the aforementioned field studies, wherein the response to CWI was examined only in one finger, the preimmersion temperature of the digit was considerably lower in the tests performed at high-altitude than in those at sea-level.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…It may appear that current results are in conflict with previous studies that have shown an enhanced cold-induced vasoconstriction during CWI of a hand at high-altitude (Daanen and van Ruiten, 2000;Mathew et al, 1977;1979;Purkayastha et al, 1999;Takeoka et al, 1993). However, in the aforementioned field studies, wherein the response to CWI was examined only in one finger, the preimmersion temperature of the digit was considerably lower in the tests performed at high-altitude than in those at sea-level.…”
Section: Discussioncontrasting
confidence: 96%
“…However, in the above studies (Daanen and van Ruiten, 2000;Mathew et al, 1977;1979;Takeoka et al, 1993;Purkayastha et al, 1999), the temperature of the digits prior to the local cold provocation was significantly lower in the hypoxic than in the normoxic cold test, despite the similar general thermal status of the subjects; this effect appears not to have been taken into account when concluding that hypoxia potentiates the cold-induced vasoconstrictor response. In view of the fact that the cold tests were performed a few hours (Daanen and van Ruiten, 2000;Mathew et al, 1977) or days (Daanen and van Ruiten, 2000;Mathew et al, 1977;1979;Takeoka et al, 1993;Purkayastha et al, 1999) after the arrival of the subjects at high altitude, the enhanced peripheral vasoconstrictor tone was probably attributable either to the distinct effects of hypoxia (Heistad and Wheeler, 1970;Kollai, 1983), or to the synergistic actions of hypoxia and low ambient temperature (Cipriano and Goldman, 1975). Considering that the response magnitude of a physiological function may be significantly affected by its basal level of activity (cf.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, the onset time is shortened. The beneficial effect of vitamin C may be attributed to its antioxidant properties, metabolic and thermogenic properties, collagen synthesis, anti-stress activity and restoration of intercellular substances as well as to better maintenance of the rheological status of the blood (Purkayastha et al 1999).…”
Section: Cold Resistance Trainingmentioning
confidence: 99%